If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(u + -7) = -4u + 18 Reorder the terms: -9(-7 + u) = -4u + 18 (-7 * -9 + u * -9) = -4u + 18 (63 + -9u) = -4u + 18 Reorder the terms: 63 + -9u = 18 + -4u Solving 63 + -9u = 18 + -4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '4u' to each side of the equation. 63 + -9u + 4u = 18 + -4u + 4u Combine like terms: -9u + 4u = -5u 63 + -5u = 18 + -4u + 4u Combine like terms: -4u + 4u = 0 63 + -5u = 18 + 0 63 + -5u = 18 Add '-63' to each side of the equation. 63 + -63 + -5u = 18 + -63 Combine like terms: 63 + -63 = 0 0 + -5u = 18 + -63 -5u = 18 + -63 Combine like terms: 18 + -63 = -45 -5u = -45 Divide each side by '-5'. u = 9 Simplifying u = 9
| 3x+4=x+6 | | -9(4-7)=4u+18 | | 7+4y=-1 | | -12x=6y | | 7(3b+1)+(22b-5)=0 | | 2(q+1)=3(q-6) | | 8x+9y=10 | | 7(m+1)=9(m+2) | | -7(3b+1)+(22b-5)=0 | | 2(q+1)=3(q-2) | | 3.7q-1.9-3.8q=-1.1q-4.9 | | -3x=-10 | | -7x=-63 | | 59-2X=7X+21 | | 14-9X=65-30X | | 2=-(n-8) | | -26X-9=7X+22 | | -4x=16 | | 5X+9=-89-9X | | 129-5X=2X+24 | | 3=-3+5(x+6) | | 10-6X=14-7X | | 56-2X=7X+20 | | 14=-2x | | 10x=130 | | 3X+14=95-6x | | 4+3X=28+X | | 2z-9=-5-2(2z+8) | | 6X+24=13X-60 | | -3(y+1)-(-2y-4)=-3 | | 10x-20=5x+5 | | 3t^2-4t+5=0 |